Correspondence and papers connected with recent occurrences in the North-West Territories [electronic resource]. - Canada. ([Ottawa? : s.n.], 1870)
Also available in French. See CIHM microfiche no. 32293. "Printed by order of Parliament." Electronic reproduction. Mode of access: Internet. 44